2003
DOI: 10.1081/scc-120026846
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Annularly Functionalized Dicationic Benzimidazolophanes and Benzotriazolophanes

Abstract: Annularly functionalized dicationic benzimidazolophanes (1, 2, and 3) and benzotriazolophanes (1a, 2a, and 3a) were synthesized by alkylation followed by double quaternization.Cationic heterophanes [1] are rapidly developing classes of cyclophanes, which mimic molecular recognition events in biological systems by apolar complexation of guest molecules in aqueous solution. Some of the important application aspects of cationic heterophanes are their ability to show increased chelating effects, solubilizing powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Chemical shifts (in ppm) were referenced with tetramethylsilane (δ = 0 ppm) in deuterated chloroform, deuterated acetone, or deuterated benzene. 13 C NMR spectra were obtained by using the same NMR spectrometers and were calibrated with CDCl 3 (δ = 77.00 ppm), (CD 3 ) 2 CO (δ = 29.84, 206.26 ppm), or C 6 D 6 (δ = 128.00 ppm). High-resolution mass spectrometry was performed on a mass spectrometer.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chemical shifts (in ppm) were referenced with tetramethylsilane (δ = 0 ppm) in deuterated chloroform, deuterated acetone, or deuterated benzene. 13 C NMR spectra were obtained by using the same NMR spectrometers and were calibrated with CDCl 3 (δ = 77.00 ppm), (CD 3 ) 2 CO (δ = 29.84, 206.26 ppm), or C 6 D 6 (δ = 128.00 ppm). High-resolution mass spectrometry was performed on a mass spectrometer.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…(Dodecyloxy)(ethyl)dimethylsilane (1b): colorless oil; 1 H NMR (400 MHz, CDCl 3 ) δ 3.50 (t, 2H, J = 6.7 Hz), 1.40−1.50 (m, 2H), 1.15−1.28 (m, 18H), 0.88 (t, 3H, J = 7.9 Hz), 0.81 (t, 3H, J = 6.8 Hz), 0.50 (q, 2H, J = 7.9 Hz), 0.01 (s, 6H); 13 (Dodecyloxy)triethylsilane (1e): colorless oil; 1 H NMR (400 MHz, (CD 3 ) 2 CO) δ 3.50 (t, 2H, J = 6.4 Hz), 1.38 (m, 2H), 1.30−1.10 (m, 18H), 0.83 (t, 9H, J = 7.9 Hz), 0.75 (t, 3H, J = 7.0 Hz), 0.47 (q, 6H, J = 7.9 Hz); 13…”
Section: General Procedures For the Deprotection Of Benzyl Ethersmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Baker et al found that in the preparation of the p -xylyl linked imidazolium cyclophanes 27-29, as the number of methyl groups on the xylyl component of the bis-azole was increased (none in 27, two in 28 and four in 29) the requirement for the use of low concentrations to avoid polymeric products decreased (Fig. 118 69% [18] n 126 n = 1 54% [16] 127 n = 2 40% [16] 128 X = CH, R = H 70% [47,48] 129 X = CH, R = Br 60% [47,48] 130 X = CH, R = CO 2 H 50% [47,48] 131 X = CH, R = CO2Me 45% [47,48] 132 X = CMe, R = H 50% [47,48] 133 X = CMe, R = Br 55% [47,48] 134 X = N, R = H 60% [34,48] 135 X = N, R = Br 57% [34,48] 136 X = N, R = CO 2 H 40% [34,48] 137 X = N, R = CO 2 Me 43% [34,48] 120 X = CH 52% [46] 121 X = N 45% [46] 122 m X = CH 48% [46] 123 m X = N 55% [46] 124 p X = CH 54% [46] 125 p X = N 54% [46] m or p m or p Fig. This result may be a consequence of the additional methyl groups restricting conformational freedom of the imidazole unit in the intermediate formed during the 3+1 synthesis, and thereby favouring cyclization over polymerization [26].…”
Section: Synthesismentioning
confidence: 99%